2016
DOI: 10.1590/2177-6709.21.6.058-066.oar
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of reliability, accuracy, sensitivity and predictive value of a subjective method to classify facial pattern in adults

Abstract: Introduction: Craniofacial pattern diagnosis is vital in Orthodontics, as it influences decision-making regarding treatment options and prognosis. Capelozza Filho proposed a subjective method for facial classification comprising five patterns: I, II, III, Long Face and Short Face. Objective:To investigate the accuracy of a subjective classification method of facial patterns applied to adults. Methods:A sample consisting of 52 adults was used for this study. Frontal and lateral view photographs were taken with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…When evaluating the method error of the 3D images used, it was observed that most of the analyses performed showed a concordance of moderate or good, attesting to the fact that the 3D images obtained by a light scanner have a satisfactory replicability for clinical use. However, this subjective diagnosis does not seem to be replicated with accuracy, a fact already reported in the literature in studies using 2D images 19,21 . A recent study has shown that Fr__nkel manoeuvre was less reproducible when performed on 3D records than on 2D pictures 22 .…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…When evaluating the method error of the 3D images used, it was observed that most of the analyses performed showed a concordance of moderate or good, attesting to the fact that the 3D images obtained by a light scanner have a satisfactory replicability for clinical use. However, this subjective diagnosis does not seem to be replicated with accuracy, a fact already reported in the literature in studies using 2D images 19,21 . A recent study has shown that Fr__nkel manoeuvre was less reproducible when performed on 3D records than on 2D pictures 22 .…”
Section: Discussionmentioning
confidence: 81%
“…However, this subjective diagnosis does not seem to be replicated with accuracy, a fact already reported in the literature in studies using 2D images. 19,21 A recent study has shown that Frӓnkel manoeuvre was less reproducible when performed on 3D records than on 2D pictures. 22 It is possible that this greater variability in 3D images can be explained by the fact that this method provides greater detail of information, including features that cannot be viewed in 2D images.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Profile I is a straight profile, and profile II presents a negative step between the maxilla and mandible corresponding to patients with mandibular retrognathism. Profile III presents a positive step between the maxilla and mandible, thereby indicating anteroposterior maxillary deficiency, mandibular prognathism, or both [ 18 ]. They were also evaluated to consider mandibular asymmetry (higher than 4 mm) and vertical facial patterns: an anterior open bite, vertical maxillary excess, and vertical maxillary deficiency.…”
Section: Data Collectionmentioning
confidence: 99%